Teachers’ implementation of translanguaging in EFL classrooms: a systematic review - Huang, X (2022)
The theory of translanguaging has been widely discussed in the field of applied linguistics both as a model to describe bilingualism and as a pedagogy. It seems promising to implement pedagogical translanguaging in various types of lessons and contexts, but little is known about the impact of pedagogical translanguaging in English language teaching (ELT) classrooms on English language proficiency among learners who learn English as a foreign language (EFL).